Secondary battery and electric equipment
By designing a double-layer structure of the positive electrode active material layer on the positive electrode sheet of the secondary battery, using fibrous conductive agents and particulate conductive agents, the serious polarization problem is solved and higher electrochemical and kinetic properties are achieved.
Patent Information
- Application Number
- CN202411830412.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-12
AI Technical Summary
When the prior art increases the energy density of secondary batteries, it is easy to cause serious polarization and poor electrochemical performance. It is necessary to improve the dynamic performance of electrode ion transport to reduce polarization and improve battery performance.
A positive electrode sheet of a secondary battery is designed, and a positive electrode active material layer with a double-layer structure is used, in which a fibrous conductive agent is used for the first active material layer close to the positive electrode current collector, and a particulate conductive agent is used for the second active material layer far away from the positive electrode current collector to promote electrolyte penetration and reduce polarization.
Through this structural design, the electrochemical performance of the secondary battery, such as the initial Coulomb efficiency and cyclic performance, is significantly improved, polarization is reduced, and the kinetic performance is improved.
Smart Images

Figure CN119650805A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new energy technology, and in particular to a secondary battery and electrical equipment. Background Art
[0002] At present, the commonly used method to improve energy density includes using thick electrodes to increase the active material loading per unit area. However, simply increasing the electrode thickness will increase the transport distance of ions and electrons, resulting in severe polarization and poor electrochemical performance. Therefore, it is necessary to develop a technology to improve the electrode ion transport kinetics, reduce polarization, and improve the electrical performance of the battery. Summary of the invention
[0003] Based on the defects of the prior art, the purpose of this application is to provide a secondary battery and an electrical device.
[0004] In order to achieve the above-mentioned object, in a first aspect, the present application provides a secondary battery, comprising a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer provided on one or both sides of the positive electrode current collector;
[0005] Along the direction away from the positive electrode current collector, the positive electrode active material layer includes a first active material layer and a second active material layer in sequence, and the first active material layer and the second active material layer both contain a conductive agent, wherein the conductive agent of the first active material layer is a fibrous conductive agent, and the conductive agent of the second active material layer is a granular conductive agent.
[0006] In some embodiments, the mass fraction of the fibrous conductive agent in the first active material layer is 0.5% to 1%.
[0007] In some embodiments, the mass fraction of the granular conductive agent in the second active material layer is ≥ 1%. In one embodiment, the mass fraction of the granular conductive agent in the second active material layer is 1% to 6%.
[0008] In some embodiments, the mass fraction of the conductive agent in the positive electrode active material layer is 0.5% to 3%.
[0009] In some embodiments, the positive electrode sheet, the separator and the negative electrode sheet are arranged in sequence and wound, the positive electrode sheet has a straight area and a corner area, the first active material layer is located in the straight area and the corner area of the positive electrode sheet, and the second active material layer is located in the straight area of the positive electrode sheet.
[0010] In some embodiments, the thickness h2 of the first active material layer and the thickness h3 of the second active material layer satisfy: h2:h3=(4-10):1.
[0011] In some embodiments, the second active material layer h3 satisfies: 10 μm≤h3≤30 μm.
[0012] In some embodiments, the average diameter of the fibrous conductive agent is less than 150 nm, and the average specific surface area is 10 to 250 m 2 / g, and an average length of 5 to 30 μm. In one embodiment, the average diameter of the fibrous conductive agent is 10 to 20 nm, and the average specific surface area is 150 to 250 m 2 / g.
[0013] In some embodiments, the Dv50 of the particulate conductive agent is 30-50 nm.
[0014] In some embodiments, the fibrous conductive agent includes at least one of carbon nanotubes and carbon fibers.
[0015] In some embodiments, the particulate conductive agent includes at least one of Ketjen black, acetylene black, and Super-P.
[0016] In a second aspect, the present application provides an electrical device including the secondary battery.
[0017] Compared with the prior art, the beneficial effect of the present application is that: by setting the positive electrode active material layer to include a double-layer structure, and controlling the conductive agent in the first active material layer close to the positive electrode current collector to be a fibrous conductive agent, and the conductive agent in the second active material layer away from the positive electrode current collector to be a granular conductive agent, the present application can promote the penetration of the electrolyte in the positive electrode material, reduce the polarization of the charge and discharge process, and make the secondary battery have good electrochemical properties such as initial coulomb efficiency and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a schematic diagram of the local structure of the winding core in Example 1;
[0019] Figure 2 Schematic diagram of gap coating in Example 1;
[0020] Figure 3 This is a microscopic schematic diagram of the double-layer structure of the straight area of the positive electrode plate in Example 1;
[0021] Among them, 10-positive electrode plate, 20-diaphragm, 30-negative electrode plate, 101-positive electrode collector, 102-first active material layer (i.e. lower layer), 103-second active material layer (i.e. upper layer), 301-negative electrode collector, 302-negative electrode active material layer. DETAILED DESCRIPTION
[0022] In order to better illustrate the purpose, technical scheme and advantages of the present application, the present application will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present application in detail, rather than to limit the present application. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. The experimental reagents and instruments involved in the implementation of this application are all commonly used ordinary reagents and instruments unless otherwise specified. In the present application, the technical features described in an open manner include closed technical schemes composed of the listed features, and also include open technical schemes containing the listed features.
[0023] According to a first aspect of the present application, a secondary battery is provided, comprising a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer provided on one or both sides of the positive electrode current collector;
[0024] Along the direction away from the positive electrode current collector, the positive electrode active material layer includes a first active material layer and a second active material layer in sequence, and the first active material layer and the second active material layer both contain a conductive agent, wherein the conductive agent of the first active material layer is a fibrous conductive agent, and the conductive agent of the second active material layer is a granular conductive agent.
[0025] By setting the positive electrode active material layer to a multilayer structure, the conductive agent in the first active material layer close to the positive electrode current collector is a fibrous conductive agent, the fibrous conductive agent has a high aspect ratio and a large specific surface area, which can promote the penetration of the electrolyte in the positive electrode material, which is beneficial to reducing the interface impedance. At the same time, the fibrous conductive agent can better improve the mechanical properties of the positive electrode material and help increase the adhesion between the positive electrode active material layer and the positive electrode current collector; the conductive agent in the second active material layer away from the positive electrode current collector is a granular conductive agent. Since the active material containing the granular conductive agent is more likely to penetrate and diffuse into the active material containing the fibrous conductive agent, the specific shape difference of the conductive agent in the first active material layer and the second active material layer is beneficial to improving the interface stability between the first active material layer and the second active material layer, and improving the problems of microcracks and peeling of the positive electrode material during the charging and discharging process. In addition, the specific shape difference of the conductive agent in the first active material layer and the second active material layer is more conducive to constructing a gradient distribution of electron transfer and ion diffusion, reducing polarization distribution, improving the utilization rate of the positive electrode active material, and improving the dynamic performance of the electrode sheet to a greater extent.
[0026] Under the combined action of the first active material layer containing a fibrous conductive agent and the second active material layer containing a granular conductive agent, the positive electrode has good electron and ion transfer kinetics, low polarization, and the secondary battery has good electrochemical properties such as initial coulomb efficiency and cycle performance.
[0027] In some embodiments, the mass fraction of the fibrous conductive agent in the first active material layer is 0.5% to 1%. For example, the mass fraction of the fibrous conductive agent in the first active material layer is 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or an interval formed by any two of the above values.
[0028] When the mass fraction of the fibrous conductive agent in the first active material layer is in the range of 0.5% to 1%, not only does the layer have good conductivity, but the fibrous conductive agent is also better dispersed in the first active material layer slurry, and the slurry also has a suitable viscosity, which makes the battery cycle performance better and the initial coulomb efficiency higher.
[0029] In some embodiments, the mass fraction of the granular conductive agent in the second active material layer is ≥ 1%. For example, the mass fraction of the granular conductive agent in the second active material layer is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, or an interval formed by any two of the above values.
[0030] When the mass fraction of the particulate conductive agent in the second active material layer is ≥1%, the conductivity of the layer is better.
[0031] In one embodiment, the mass fraction of the particulate conductive agent in the second active material layer is 1% to 6%.
[0032] In some embodiments, the mass fraction of the conductive agent in the positive electrode active material layer is 0.5% to 3%. For example, the mass fraction of the conductive agent in the positive electrode active material is 0.5%, 0.7%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3% or an interval formed by any two of the above values.
[0033] When the mass fraction of the conductive agent in the positive electrode active material layer is in the range of 0.5% to 3%, it is beneficial to reduce the electrode contact resistance and promote the infiltration of the electrolyte while ensuring that the secondary battery has a high energy density. It is also beneficial to improve the toughness of the positive electrode sheet and improve the battery charging and discharging efficiency.
[0034] In some embodiments, the positive electrode sheet, the separator and the negative electrode sheet are arranged in sequence and wound, the positive electrode sheet has a straight area and a corner area, the first active material layer is located in the straight area and the corner area of the positive electrode sheet, and the second active material layer is located in the straight area of the positive electrode sheet.
[0035] The positive electrode sheet, separator and negative electrode sheet are arranged in sequence and wound to form a wound battery cell. For wound batteries (i.e., cores), simply increasing the electrode thickness will also increase the CB value in the corner area, causing the risk of lithium plating. By simultaneously setting the first active material layer and the second active material layer in a specific position order in the straight area of the positive electrode sheet, it is ensured that the straight area has good electron and ion transfer kinetics and is conducive to obtaining a more stable interface; the first active material layer is set in the corner area of the positive electrode sheet, but the second active material layer is not set. Compared with the granular conductive agent, the fibrous conductive agent has better conductivity, lower impedance, and stronger liquid absorption and liquid retention ability, which can better reduce the risk of lithium plating caused by the increase in CB value difference in the corner area and improve the cycle performance.
[0036] In one of the embodiments, the second active material layer is made by gap coating, the gap is the length of the corner area of the positive electrode plate, and the core satisfies ab=π*(h1+2*h2), where a is the gap length on the outside of the core, b is the gap length on the inside of the core, h1 is the thickness of the positive electrode collector, h2 is the thickness of the first active material layer, and the units of a, b, h1 and h2 are the same, such as mm.
[0037] In some embodiments, the thickness h2 of the first active material layer and the thickness h3 of the second active material layer satisfy: h2:h3=(4-10):1. For example, h2:h3 is 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1 or an interval formed by any two of the above values.
[0038] Controlling h2:h3 within the range of (4-10):1, so that the first active material layer and the second active material layer have a more suitable thickness ratio, which is conducive to better performance of the two functions, and makes the secondary battery have better dynamic performance and interface adhesion. When the positive electrode sheet, the separator and the negative electrode sheet are arranged in sequence and wound, the positive electrode sheet has a straight area and a corner area, the first active material layer is located in the straight area and the corner area of the positive electrode sheet, and the second active material layer is located in the straight area of the positive electrode sheet, controlling h2:h3 within the range of (4-10):1 can also ensure that the corner area of the positive electrode sheet has a higher active material capacity and better electrolyte infiltration, better cycle performance, and higher initial coulomb efficiency.
[0039] In some embodiments, the second active material layer h3 satisfies: 10 μm≤h3≤30 μm. For example, h3 is 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, 22 μm, 24 μm, 26 μm, 28 μm, 30 μm, or an interval formed by any two of the above values.
[0040] When h3 is in the range of 10μm to 30μm, it is conducive to forming a gap in the corner area of the positive and negative electrode sheets, alleviating the squeezing of adjacent layers caused by the expansion of the electrode sheets in the corner area, and at the same time better promoting the infiltration and liquid retention capacity of the electrolyte in the corner area. Moreover, the interface stability between the first active material layer and the second active material layer in the straight area is better, which can ensure the construction of the double-layer electron and ion transport gradient in the straight area, better cycle performance, and higher initial coulomb efficiency.
[0041] In some embodiments, the average diameter of the fibrous conductive agent is less than 150 nm, and the average specific surface area is 10 to 250 m 2 / g, and the average length is 5 to 30 μm. For example, the average diameter of the fibrous conductive agent is 150 nm, 140 nm, 130 nm, 120 nm, 110 nm, 100 nm, 90 nm, 80 nm, 70 nm, 60 nm, 50 nm, 40 nm, 30 nm, 20 nm, 10 nm or the interval formed by any two of the above values; the average specific surface area is 10 m 2 / g, 20m 2 / g, 30m 2 / g, 40m 2 / g, 50m 2 / g, 60m 2 / g, 70m 2 / g, 80m 2 / g, 90m 2 / g、100m 2 / g, 120m 2 / g, 140m 2 / g, 160m 2 / g, 180m 2 / g, 200m 2 / g, 220m 2 / g, 250m 2 / g or the interval formed by any two of the above values; the average length is 5μm, 7μm, 10μm, 12μm, 15μm, 17μm, 20μm, 22μm, 25μm, 27μm, 30μm or the interval formed by any two of the above values.
[0042] When the average diameter of the fibrous conductive agent is below 150nm and the average specific surface area is between 10 and 250m 2 / g range, and the average length is in the range of 5 to 30 μm. The fibrous conductive agent has a high specific surface area, good conductivity, and a high aspect ratio, which is beneficial to improving the tensile strength of the positive electrode sheet and better improving the problems of microcracks and peeling caused by volume changes during charging and discharging. In one embodiment, the average diameter of the fibrous conductive agent is 10 to 20 nm, and the average specific surface area is 150 to 250 m2 / g, so that the conductivity is better and the fibrous conductive agent has better dispersion in the first active material layer, which makes the battery cycle performance better and the initial coulomb efficiency higher.
[0043] The average diameter and length of the fibrous conductive agent can be tested by transmission electron microscopy (TEM) or scanning electron microscopy (SEM). With the help of software, the diameter or length of the obtained sample can be counted and the average value can be calculated. Generally, the number of fibrous conductive agents measured is 100 to 200.
[0044] The average specific surface area is calculated by the BET test method. The adsorption of nitrogen by the test sample at different relative pressures is used to calculate the specific surface area of the material according to the BET formula.
[0045] In some embodiments, the Dv50 of the granular conductive agent is 30-50 nm. For example, the Dv50 of the granular conductive agent is 30 nm, 32 nm, 34 nm, 36 nm, 38 nm, 40 nm, 42 nm, 44 nm, 46 nm, 48 nm, 50 nm, or an interval formed by any two of the above values.
[0046] When the Dv50 of the granular conductive agent is in the range of 30 to 50 nm, the specific surface area is larger, and it is easier to fill the small gaps between the positive electrode active materials, so that the formed conductive network has better continuity, thereby better improving the conductivity of the positive electrode sheet.
[0047] The Dv50 of a granular conductive agent refers to the particle size corresponding to when the cumulative volume percentage of the granular conductive agent reaches 50%, that is, the median particle size of the volume distribution. The particle size distribution is tested by laser particle size analysis. The particle size distribution of the sample is characterized by laser light scattering technology, and the Dv50 particle size of the sample is calculated.
[0048] In some embodiments, the fibrous conductive agent includes at least one of carbon nanotubes (CNT) and carbon fibers (VGCF). In one embodiment, the fibrous conductive agent includes carbon nanotubes. Compared with carbon fibers, carbon nanotubes have a higher aspect ratio, a larger specific surface area, and a higher tensile strength, which is beneficial for reducing impedance and improving mechanical properties; at the same time, it is more conducive to the construction of an electron and ion transport gradient network, promotes the penetration of electrolyte in the positive electrode material, and improves kinetic performance.
[0049] In one embodiment, the average diameter of the carbon nanotubes is less than 20 nm, and the average specific surface area is 150-250 m 2 / g, and the average length is 5-30μm. The average diameter of carbon nanotubes can be selected as 20nm, 18nm, 16nm, 14nm, 12nm, 10nm or the interval formed by any two of the above values; the average specific surface area is 150m 2 / g, 160m 2 / g, 170m 2 / g, 180m 2 / g, 190m 2 / g, 200m 2 / g, 210m 2 / g, 220m 2 / g, 230m 2 / g, 240m 2 / g, 250m 2 / g or the interval formed by any two of the above values; the average length is 5μm, 7μm, 10μm, 12μm, 15μm, 17μm, 20μm, 22μm, 25μm, 27μm, 30μm or the interval formed by any two of the above values.
[0050] The average diameter of carbon nanotubes is controlled to be below 20nm, and the average specific surface area is 150-250m 2 / g, especially controlling the average diameter of carbon nanotubes to be 10-20nm and the average specific surface area to be 150-250m 2 / g, while ensuring good dispersion of carbon nanotubes, the conductivity is better.
[0051] In one embodiment, the average diameter of the carbon fibers is 150 nm and the average specific surface area is 13 m 2 / g, with an average length of 10-20μm. Although the specific surface area and aspect ratio of carbon fiber are inferior to those of carbon nanotubes, the production is mature and the dispersion is slightly better than that of carbon nanotubes. When the first active material layer contains carbon nanotubes, the mass fraction of carbon fiber in the first active material layer can be selected to be 1% to make the layer have better conductivity.
[0052] In some embodiments, the particulate conductive agent includes at least one of Ketjen black, acetylene black, and Super-P (ie, SP).
[0053] In some embodiments, the first active material layer further comprises a positive electrode active material. The positive electrode active material in the first active material layer can be selected from any commonly used positive electrode active material in the art. Exemplarily, the positive electrode active material in the first active material layer includes at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, transition metal phosphate, and lithium iron phosphate.
[0054] In some embodiments, the first active material layer further comprises a binder. The binder in the first active material layer may select any commonly used binder in the art. Exemplarily, the binder in the first active material layer includes at least one of polyvinylidene fluoride (PVDF) and carboxylated polyvinylidene fluoride (C-PVDF). The mass fraction of the binder in the first active material layer may be selected as 1% to 2%, such as 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% or the interval range formed by any two of the above values.
[0055] In some embodiments, the second active material layer further comprises a positive electrode active material. The positive electrode active material in the second active material layer can be selected from any commonly used positive electrode active material in the art. Exemplarily, the positive electrode active material in the second active material layer includes at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, transition metal phosphate, and lithium iron phosphate.
[0056] In some embodiments, the second active material layer further comprises a binder. The binder in the second active material layer can select any commonly used binder in the art. Exemplarily, the binder in the second active material layer includes at least one of polyvinylidene fluoride (PVDF) and carboxylated polyvinylidene fluoride (C-PVDF). The mass fraction of the binder in the second active material layer can be selected as 1% to 2%, such as 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% or the interval range formed by any two of the above values.
[0057] The mass fraction of the positive electrode active material in the positive electrode active material layer can be selected to be 96% to 98%, such as 96%, 96.2%, 96.4%, 96.6%, 96.8%, 97%, 97.2%, 97.4%, 97.6%, 97.8%, 98% or an interval formed by any two of the above values.
[0058] In some embodiments, the positive electrode current collector may be any metal foil or composite current collector commonly used in the art, such as aluminum foil or composite aluminum foil.
[0059] In some embodiments, a conductive primer layer is provided between the positive current collector and the positive active material layer to enhance the interfacial conductivity between the positive current collector and the positive active material layer and reduce the DC internal resistance. However, the conductive primer layer is not a necessary structure of the positive electrode sheet of the present application.
[0060] In some embodiments, the compaction density of the positive electrode sheet is 3.4 to 4.3 g / cm 3 For example, the compaction density of the positive electrode is 3.4g / cm3 、3.5g / cm 3 、3.6g / cm 3 、3.7g / cm 3 、3.8g / cm 3 、3.9g / cm 3 , 4g / cm 3 , 4.1g / cm 3 , 4.2g / cm 3 , 4.3g / cm 3 Or the interval formed by any two of the above values.
[0061] In some embodiments, the method for preparing the positive electrode sheet comprises the following steps:
[0062] Respectively mixing and dispersing the raw materials for preparing the first active material layer and the raw materials for preparing the second active material layer to obtain a first active material layer slurry and a second active material layer slurry;
[0063] According to the structural design of the positive electrode sheet, the first active material layer slurry is coated on the positive electrode collector, dried, and then the second active material layer slurry is coated, dried, and then rolled to obtain the positive electrode sheet.
[0064] In one embodiment, the solid content of the first active material layer slurry is 60wt.% to 70wt.%, such as 60wt.%, 62wt.%, 64wt.%, 66wt.%, 68wt.%, 70wt.% or an interval formed by any two of the above values.
[0065] In one embodiment, the solvent of the first active material layer slurry includes at least one of N-methylpyridone (NMP) and polyvinylidene fluoride (PVDF).
[0066] In one embodiment, the solid content of the second active material layer slurry is 60wt.% to 70wt.%, such as 60wt.%, 62wt.%, 64wt.%, 66wt.%, 68wt.%, 70wt.% or an interval formed by any two of the above values.
[0067] In one embodiment, the solvent of the second active material layer slurry includes at least one of N-methylpyridone (NMP) and polyvinylidene fluoride (PVDF).
[0068] The above-mentioned diaphragm can be selected from any commonly used diaphragm material in the art.
[0069] The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer, wherein the negative electrode current collector can be any commonly used negative electrode current collector in the art; and the negative electrode active material layer can be any commonly used negative electrode active material layer in the art.
[0070] The above-mentioned electrolyte can be any commonly used electrolyte in the art.
[0071] According to a second aspect of the present application, there is provided an electric device, comprising the above-mentioned secondary battery. The above-mentioned secondary battery can be used as a power supply for the electric device. Exemplarily, the electric device comprises at least one of an electric car and a mobile phone battery.
[0072] The present application is further described below in conjunction with specific embodiments.
[0073] Example 1
[0074] This embodiment provides a secondary battery, including a positive electrode sheet 10, a separator 20, a negative electrode sheet 30 and an electrolyte. The positive electrode sheet 10, the separator 20 and the negative electrode sheet 30 are arranged in sequence and wound to form a winding core. The partial structural schematic diagram of the winding core is shown in FIG. Figure 1 As shown;
[0075] The positive electrode sheet 10 includes a positive electrode current collector 101 and positive electrode active material layers disposed on both sides of the positive electrode current collector 101. The compaction density of the positive electrode sheet 10 is 3.55 g / cm 3 ;
[0076] The positive electrode current collector 101 is aluminum foil, and the thickness h1 of the positive electrode current collector 101 is 10 μm;
[0077] Along the direction away from the positive electrode current collector 101 , the positive electrode active material layer includes a first active material layer 102 and a second active material layer 103 in sequence;
[0078] The thickness h2 of the first active material layer 102 and the thickness h3 of the second active material layer 103 are shown in Table 1;
[0079] The requirements of the winding core are shown in Table 1, where a is the gap length on the outside of the winding core (i.e., the length of the arc outside the corner area of the positive electrode sheet), and b is the gap length on the inside of the winding core (i.e., the length of the arc inside the corner area of the positive electrode sheet), and the units of a and b are μm;
[0080] The negative electrode sheet 30 is a graphite negative electrode sheet, including a negative electrode current collector 301 and a negative electrode active material layer 302 arranged on both sides of the negative electrode current collector 301, wherein the negative electrode current collector 301 is a copper foil with a thickness of 8 μm, and the negative electrode active material layer 302 contains the following components by mass fraction: artificial graphite 95%, conductive agent SP 1.5%, thickener CMC (sodium carboxymethyl cellulose) 2%, binder SBR (styrene butadiene rubber) 2%, and the compaction density of the negative electrode sheet 30 is 1.6 g / cm 3 ;
[0081] The diaphragm 20 adopts PP-PE-PP composite diaphragm Celgard 2325;
[0082] The electrolyte used a mixed solvent of EC / FEC / EMC / DMC (weight ratio 3:1:2:4) and added 1.2 mol / L LiPF6.
[0083] The method for preparing the secondary battery of this embodiment comprises the following steps:
[0084] The positive electrode active material, the binder and the conductive agent were mixed with N-methylpyridone (NMP) according to the formula in Table 1, stirred and dispersed to obtain a first active material layer 102 slurry with a solid content of 65 wt.% and a second active material layer 103 slurry with a solid content of 65 wt.%, wherein the positive electrode active material is NCA (LiNi 0.8 Co 0.15 Al 0.05 O2), the binder is polyvinylidene fluoride (PVDF);
[0085] The first active material layer 102 slurry is coated on both sides of the positive electrode current collector by roller coating, and dried at 85° C., and then the second active material layer 103 slurry is coated at preset gap lengths a and b, and then dried at 85° C. and compacted to obtain a positive electrode sheet 10;
[0086] The positive electrode sheet 10, the separator 20 and the negative electrode sheet 30 are wound together into a bare battery cell, placed in a soft-pack shell, and then sealed and formed after injecting electrolyte to obtain a lithium-ion secondary battery.
[0087] Table 1
[0088]
[0089] Table 2
[0090]
[0091] Embodiments 2 to 4
[0092] These embodiments all provide a secondary battery, and the differences between these secondary batteries and Embodiment 1 are as follows: the contents of the components in the first active material layer 102 are different;
[0093] The differences between the preparation methods of these secondary batteries and those of Example 1 are as follows: the ratios of the positive electrode active material, the binder and the conductive agent in the slurry of the first active material layer 102 are different, see Table 1 for details.
[0094] Embodiments 5 to 8
[0095] These embodiments all provide a secondary battery, and the differences between these secondary batteries and Embodiment 1 are as follows: the thickness h2 of the first active material layer 102 and the thickness h3 of the second active material layer 103 are different, see Table 1 for details;
[0096] The difference between the preparation methods of these secondary batteries and Example 1 is as follows: the coating amounts of the slurry of the first active material layer 102 and the slurry of the second active material layer 103 are adjusted accordingly.
[0097] Examples 9 to 12
[0098] These embodiments all provide a secondary battery, and the differences between these secondary batteries and Embodiment 1 are as follows: the thickness h3 of the second active material layer 103 is different, see Table 1 for details;
[0099] The difference between the preparation methods of these secondary batteries and Example 1 is as follows: the coating amount of the slurry of the second active material layer 103 is adjusted accordingly.
[0100] Embodiment 13
[0101] This embodiment provides a secondary battery, which is different from the embodiment 1 as follows: a and b are different, see Table 1 for details;
[0102] The difference between the preparation method of the secondary battery in this embodiment and that in the first embodiment is as follows: the slurry coating method of the second active material layer 103 is different, and the coating method in this embodiment is continuous.
[0103] Embodiments 14 to 19
[0104] These embodiments all provide a secondary battery, and the differences between these secondary batteries and Embodiment 1 are as follows: the average diameter, average specific surface area, average length and / or type of the fibrous conductive agent are different, see Tables 1 and 2 for details;
[0105] The difference between the preparation methods of these secondary batteries and Example 1 is as follows: the raw materials of the fibrous conductive agent are adjusted accordingly.
[0106] Embodiment 20-21
[0107] These embodiments all provide a secondary battery, and the differences between these secondary batteries and Embodiment 1 are as follows:
[0108] The contents of the components in the first active material layer 102 are different.
[0109] The contents of the components in the second active material layer 103 are different.
[0110] The types, Dv50 and average specific surface area of granular conductive agents are different, see Tables 1 and 2 for details.
[0111] The content of the conductive agent in the positive electrode active material layer and the content of the positive electrode active material are different, as shown in Tables 1 and 2;
[0112] The differences between the preparation methods of these secondary batteries and those of Example 1 are as follows:
[0113] The ratios of the positive electrode active material, the binder and the conductive agent in the slurry of the first active material layer 102 are different, as shown in Tables 1 and 2;
[0114] The ratios of the positive electrode active material, the binder and the conductive agent in the second active material layer slurry 103 are different, see Tables 1 and 2 for details;
[0115] Make corresponding adjustments to the granular conductive agent raw materials used.
[0116] Comparative Example 1
[0117] This comparative example provides a secondary battery, which differs from Example 1 as follows:
[0118] The conductive agent in the first active material layer 102 is different. The conductive agent in the first active material layer 102 of this comparative example is the granular conductive agent in Example 1;
[0119] The difference between the preparation method of the secondary battery in this comparative example and that in Example 1 is as follows: the conductive agent used in the slurry of the first active material layer 102 is adjusted accordingly.
[0120] Comparative Example 2
[0121] This comparative example provides a secondary battery, which differs from Example 1 as follows:
[0122] The conductive agent in the second active material layer 103 is different. The conductive agent in the second active material layer 103 of this comparative example is the fibrous conductive agent in Example 1;
[0123] The difference between the preparation method of the secondary battery in this comparative example and that in Example 1 is as follows: the conductive agent used in the slurry of the second active material layer 103 is adjusted accordingly.
[0124] Comparative Example 3
[0125] This comparative example provides a secondary battery, which differs from Example 1 as follows:
[0126] The conductive agents in the first active material layer 102 and the second active material layer 103 are different. In this comparative example, the conductive agents in the first active material layer 102 and the second active material layer 103 are the same, which are a mixture of a fibrous conductive agent and a granular conductive agent, wherein the weight ratio of the fibrous conductive agent to the granular conductive agent is 80:20, and the fibrous conductive agent and the granular conductive agent are the same as those in Example 1;
[0127] The difference between the preparation method of the secondary battery in this comparative example and that in Example 1 is as follows: the conductive agent used in the slurry of the first active material layer 102 and the slurry of the second active material layer 103 is adjusted accordingly.
[0128] Comparative Example 4
[0129] This comparative example provides a secondary battery, which differs from Example 1 as follows:
[0130] The conductive agents in the first active material layer 102 and the second active material layer 103 are different. In this comparative example, the conductive agent in the first active material layer 102 is a granular conductive agent, and the conductive agent in the second active material layer 103 is a fibrous conductive agent. The fibrous conductive agent and the granular conductive agent are the same as those in Example 1.
[0131] The difference between the preparation method of the secondary battery in this comparative example and that in Example 1 is as follows: the conductive agent used in the slurry of the first active material layer 102 and the slurry of the second active material layer 103 is adjusted accordingly.
[0132] The above lithium-ion secondary battery was subjected to the following performance tests:
[0133] Initial coulombic efficiency: At 25°C, charge the lithium-ion secondary battery at a constant current of 0.2C to 4.3V, then charge at a constant voltage of 4.3V until the current is less than 0.02C, let it stand for 5 minutes, and discharge at 0.2C to 2.8V. Calculate the initial coulombic efficiency of the battery after three cycles.
[0134] Impedance test: At 25°C, test the battery at 50% SOC, 10mHz~10 5 AC impedance spectroscopy (EIS) in the Hz frequency range, calculation of ohmic impedance R0;
[0135] Cycle test: At 45°C, the battery was charged at a constant current of 1C to 4.3V, then charged at a constant voltage of 4.3V until the current was less than 0.02C, left to stand for 5 minutes, and discharged at 1C to 2.8V for cycling.
[0136] The test results are shown in Table 3.
[0137] Table 3
[0138]
[0139] It can be seen from the above data that the secondary batteries of each embodiment have higher initial coulombic efficiency, lower impedance and better cycle performance, such as the initial coulombic efficiency is above 81.9%, R0 is below 0.392Ω, and the 45°C 500 cycle capacity retention rate is above 90%, and the comprehensive performance is better than that of the comparative examples.
[0140] By comparing Example 1 with Comparative Examples 1 to 4, it can be seen that when the conductive agent in the first active material layer 102 is a fibrous conductive agent and the conductive agent in the second active material layer 103 is a granular conductive agent, while obtaining a lower impedance, the initial coulomb efficiency and cycle performance are significantly improved; in Comparative Example 1, the conductive agents in the first active material layer 102 and the second active material layer 103 are both granular conductive agents, and the initial coulomb efficiency, impedance and cycle performance are all poor. This is because the penetration ability of the electrolyte in the positive electrode active material layer is weak, and there is an incomplete infiltration phenomenon, which causes more side reactions during the cycle, especially in the initial cycle. At the same time, the adhesion between the first active material layer 102 and the positive electrode current collector is weak, and the interface stability deviation between the first active material layer 102 and the second active material layer 103 makes it easy for the positive electrode active material layer to have micro- There are problems such as cracks and peeling, the polarization of the positive electrode active material layer is also large, and the conductivity of the granular conductive agent is biased relative to the fibrous conductive agent; in comparative example 2, the conductive agent in the first active material layer 102 and the second active material layer 103 are both fibrous conductive agents, and the initial coulomb efficiency is biased. This is because the uniformly distributed conductive agent cannot form a gradient structure for electronic and ion conduction. There is an uneven distribution of lithium ions and electrons during the charge and discharge process, which will cause more lithium ions to undergo side reactions at the interface to form SEI film; in comparative example 3, the conductive agent in the first active material layer 102 and the second active material layer 103 are both a mixture of fibrous conductive agent and granular conductive agent, and the initial coulomb efficiency is still biased; in comparative example 4, the conductive agent in the first active material layer 102 is a granular conductive agent, and the conductive agent in the second active material layer 103 is a fibrous conductive agent, and the initial coulomb efficiency is also biased.
[0141] By comparing Examples 1 to 4, it can be seen that when the mass fraction of the fibrous conductive agent in the first active material layer 102 is in the range of 0.5% to 1%, the conductivity of the conductive agent is higher and the slurry viscosity and dispersibility are better, the fibrous conductive agent is more evenly distributed in the first active material layer, the cycle performance is better, and the initial coulombic efficiency is higher.
[0142] By comparing Examples 1 and 5 to 8, it can be seen that when h2:h3 is in the range of (4 to 10):1, while ensuring higher conductivity, the electrolyte infiltration in the corner area is better, the cycle performance is better, and the initial coulombic efficiency is higher.
[0143] By comparing Examples 1 and 9 to 12, it can be seen that when h3 is in the range of 10 μm to 30 μm, the interface stability between the first active material layer and the second active material layer is better, which can ensure the construction of the double-layer electron and ion transport gradient in the straight region, and the cycle performance is better, while the initial coulomb efficiency is higher.
[0144] By comparing Example 1 with Example 13, it can be seen that when the first active material layer 102 is located in the straight area and corner area of the positive electrode plate, and the second active material layer 103 is located in the straight area of the positive electrode plate, that is, when the second active material layer 103 slurry is intermittently coated, the cycle performance is significantly better, thereby making the overall performance of the battery better.
[0145] Comparison of Examples 1, 14 to 17 shows that when the average diameter of the fibrous conductive agent is in the range of 10 to 20 nm and the average specific surface area is in the range of 150 to 250 m 2 / g range, the conductivity of the conductive agent is higher and the slurry viscosity and dispersibility are better, the fibrous conductive agent is more evenly distributed in the first active material layer, the cycle performance is better, and the initial coulombic efficiency is higher.
[0146] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A secondary battery, characterized in that: It comprises a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer arranged on one or both sides of the positive electrode current collector; Along the direction away from the positive electrode current collector, the positive electrode active material layer includes a first active material layer and a second active material layer in sequence, and the first active material layer and the second active material layer both contain a conductive agent, wherein the conductive agent of the first active material layer is a fibrous conductive agent, and the conductive agent of the second active material layer is a granular conductive agent.
2. The secondary battery according to claim 1, wherein: The mass fraction of the fibrous conductive agent in the first active material layer is 0.5% to 1%; and / or The mass fraction of the particulate conductive agent in the second active material layer is ≥ 1%.
3. The secondary battery according to claim 1, wherein: The mass fraction of the particulate conductive agent in the second active material layer is 1% to 6%.
4. The secondary battery according to claim 1, wherein: The mass fraction of the conductive agent in the positive electrode active material layer is 0.5% to 3%.
5. The secondary battery according to claim 1, wherein: The positive electrode sheet, the separator and the negative electrode sheet are arranged in sequence and wound, the positive electrode sheet has a straight area and a corner area, the first active material layer is located in the straight area and the corner area of the positive electrode sheet, and the second active material layer is located in the straight area of the positive electrode sheet.
6. The secondary battery according to claim 1, wherein: The thickness h2 of the first active material layer and the thickness h3 of the second active material layer satisfy: h2:h3=(4-10):
1.
7. The secondary battery according to any one of claims 1 to 6, wherein The second active material layer h3 satisfies: 10 μm≤h3≤30 μm.
8. The secondary battery according to any one of claims 1 to 6, wherein The average diameter of the fibrous conductive agent is less than 150 nm, and the average specific surface area is 10 to 250 m 2 / g, and an average length of 5 to 30 μm; preferably, the average diameter of the fibrous conductive agent is 10 to 20 nm, and the average specific surface area is 150 to 250 m 2 / g; and / or The Dv50 of the granular conductive agent is 30 to 50 nm.
9. The secondary battery according to any one of claims 1 to 6, wherein The fibrous conductive agent comprises at least one of carbon nanotubes and carbon fibers; and / or The particulate conductive agent includes at least one of Ketjen black, acetylene black and Super-P.
10. An electrical device, characterized in that: The electric device comprises the secondary battery according to any one of claims 1 to 9.
Citation Information
Patent Citations
Positive electrode pole piece and preparation method and purpose thereof
CN109546080A
Preparation method of positive electrode piece of lithium-ion battery and positive electrode piece thereof
CN110071292A
Electrochemical device and electronic device
CN111916845A
Battery cell
CN114464771A
Positive pole piece, preparation method thereof and lithium ion battery
CN117613239A